Association between severity of hypoglycemia and loss of heart rate variability in patients with type 1 diabetes mellitus. Issue 2 (1st August 2016) - Silva, Ticiana Paes; Rolim, Luiz Clemente; Sallum Filho, Celso; Zimmermann, Livia M.; Malerbi, Fernando; Dib, Sergio Atala
Abstract: Background: The occurrence of hypoglycemia has been associated with the presence of cardiovascular autonomic neuropathy. Cardiovascular autonomic reflex tests are the gold standard diagnostic method for cardiovascular autonomic neuropathy. Nevertheless, impaired heart rate variability indices on spectral analysis have been reported before cardiovascular autonomic reflex test abnormalities arise. The objective of the present study was to analyse the association between the severity of hypoglycemia and indices of heart rate variability on spectral analysis. Methods: Consecutive type 1 diabetes patients were prospectively enrolled. Heart rate variability indices were assessed by spectral analysis. One abnormal test result was used to define impaired spectral analysis. The severity of hypoglycemia was evaluated by a hypoglycemia score and patients were classified into absent/minor or moderate/severe hypoglycemia groups. Results: Patients with moderate/severe hypoglycemia were older, had longer duration of diabetes and had higher rates of diabetic complications. After adjusting for baseline clinical characteristics, impaired spectral analysis (OR: 3.85; 95% IC 1.23 – 12.02; p  = 0.020), nephropathy (OR: 4.15, 95% IC 1.27 – 13.54; p  = 0.018) and macrovascular complications (OR: 12.18, 95% IC 1.14 – 129.84; p  = 0.038) remained independent predictors of moderate/severe hypoglycemia. Patients with moderate/severe hypoglycemia had lower heart rate variability in the high frequency band of spectral analysis, reflecting a decreased parasympathetic tonus on the heart. These patients also had higher low frequency/high frequency ratios, ultimately denoting the occurrence of cardiovascular autonomic imbalance. Conclusions: Impaired heart rate variability on spectral analysis, nephropathy and macrovascular complication were shown to independently predict moderate/severe hypoglycemia. Patients with moderate/severe hypoglycemia showed loss of the cardio protective effect of vagal activity according to spectral analysis. Copyright © 2016 John Wiley & Sons, Ltd.